Eestlaste sõjalised kohustused keskajal [Military Obligations of Estonians during the Middle Ages] - Lätte, Mart (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2011)
By the beginning of the 13th century, the social structure in the Estonian territorial area had reached the early stages of feudalism. Social stratification in Estonian was based upon ownership of land and military prestige. The leading positions in Estonian society were held by nobles, who were, both, the biggest landowners, and also, the local warlords. Natural social development, in this region, was disrupted by the arrival of German and Danish crusaders on the eastern shore of the Baltic Sea. The result was, that the local native populations, including Estonians, were subjugated and, at least formally, Christianized. Nevertheless, at first, no major social changes took place. The Christian religion, generally, remained distant and alien for the local people. And the local nobles retained their social role in the administrating of some areas. Several local nobles were probably made liege lords in the new power structure, and, in time, became Germanized. The fact is that the local people did not succumb to the Germans unconditionally, but on the basis of mutual agreements.These agreements called upon the local population to fulfill Christian commitments, including military service for the Germans. Military service had been, even before the region was conquered, every freeman’s obligation. And, in their military endeavours, the Germans, quite quickly, began to demand that the local subjugated populations provide them with appropriate support. In 1207, the Livonians and Latvians were forced, under threat of being fined, to participate in the Germans’ military expeditions. When the Germans arrived on Estonian territory, the Estonians were also encompassed by this system. Already in 1217, Southern Estonians, who had been subjugated by this time, participated in a military expedition into still unconquered Northern Estonia. In various areas, military service differed. In border and coastal areas, military obligations probably played a bigger role. Just as in the overall community itself, military obligations could be quite different. Some peasants had to show up for military service better equipped than others. This was probably due to the fact that they owned bigger plots of land, and had a different legal status. Military service consisted of participating in territorial defence operations and in military expeditions abroad. On the basis of historical sources, it can be concluded that military service for territorial defence was obligatory, either on foot, or on horseback, for all men capable of bearing arms. Military expeditions abroad were conducted on horseback. And it can be assumed that participants were selected on the basis of their land ownership and financial situation – along rode those who could aff ord better arms and armour. In the 15th century, the Germans started to make less use of the local populations in their military endeavours, which was probably brought about by the professionalization of warfare, and the spread of the use of mercenary forces. In the second half of the 15th century, the local peasants participated only in territorial defence. And, by the end of the century, attempts were made to replace their military obligations with monetary payments, so that mercenaries could be hired. In 1507, limits were instituted upon the rights of peasants to bear arms in public. Nevertheless, the peasants retained a certain role in territorial defence. At the beginning of the Livonian War (1558–1583), local peasants were again used in the conquerors’ armies. In addition to participating in military expeditions, the military obligations of the local peasants also included the building and manning of the conquerors’ fortresses. Also, convoy duty for the transporting of military supplies needed for military operations. The local populations probably served as mounted infantry – they fought on foot, but travelled on horseback. These forces were recruited and led by the ruler’s officials, who functioned through the local elders. In the military, the peasants served as guides, and, probably, also as scouts. In battle, they fought as the advance and rear guard, as well as on the flanks. In the course of long-range military expeditions, the local peasant recruits were in charge of obtaining provisions, as well as of pillaging. The actual role and signifi cance of the local peasantry in Livonian military aff airs has been evaluated in many different ways. Some have stressed the minimal military usefulness of the local peasants, but this attitude is debateable. In historical chronicles, it can be seen that, despite the fact that the local peasants were, in battles, the weak link of the Christian forces, as effi cient pillagers, they served an essential function in the warfare being conducted in the region. Plus, there are sources that highly praise the cohorts recruited from amongst the local peasantry. There is very little information concerning the size of the forces consisting of Estonians and other local nationalities. But, it can be assumed that the Estonian, Livonian, Latvian, Couronian cohorts formed, numerically, the majority of the German military forces. Thus, the local peasants were essential in counterbalancing the numerical superiority of the Germans’ opponents, the Russians and Lithuanians. Therefore, it can be stated that Livonia’s subjugated nationalities played an essential role in local military aff airs. Th e fact that these local nationalities were militarily necessary was, probably, the reason why major changes were not immediately implemented in their social structures. The life of the peasantry did not begin to essentially worsen until the local nationalities had lost their military importance.